2010
DOI: 10.1016/j.devcel.2010.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Hemocyte-Secreted Type IV Collagen Enhances BMP Signaling to Guide Renal Tubule Morphogenesis in Drosophila

Abstract: SummaryDetails of the mechanisms that determine the shape and positioning of organs in the body cavity remain largely obscure. We show that stereotypic positioning of outgrowing Drosophila renal tubules depends on signaling in a subset of tubule cells and results from enhanced sensitivity to guidance signals by targeted matrix deposition. VEGF/PDGF ligands from the tubules attract hemocytes, which secrete components of the basement membrane to ensheath them. Collagen IV sensitizes tubule cells to localized BMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
139
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(146 citation statements)
references
References 96 publications
7
139
0
Order By: Relevance
“…Restriction of BMP movement may also be important in other contexts, including several where collagen IV was already shown to regulate a shortrange Dpp signal, such as the ovarian stem cell niche and the tip of malpighian tubules (8,28). The basic collagen IV binding motif is highly conserved among the Dpp/BMP2/4 subfamily (20) and is also found in some other BMPs, including BMP3, consistent with reports that BMP3 and BMP4 can bind collagen IV (11,29).…”
Section: Discussionsupporting
confidence: 64%
“…Restriction of BMP movement may also be important in other contexts, including several where collagen IV was already shown to regulate a shortrange Dpp signal, such as the ovarian stem cell niche and the tip of malpighian tubules (8,28). The basic collagen IV binding motif is highly conserved among the Dpp/BMP2/4 subfamily (20) and is also found in some other BMPs, including BMP3, consistent with reports that BMP3 and BMP4 can bind collagen IV (11,29).…”
Section: Discussionsupporting
confidence: 64%
“…Indeed, BrĂŒckner et al (2004) predicted that many phenotypes found in Pvr mutants might be indirect consequences of hemocyte dysfunction. This has certainly been borne out in independent studies of central nervous system development (Olofsson and Page, 2005;Sears et al, 2003), malpighian tubule morphogenesis (Bunt et al, 2010), and now dorsal closure. Yet, sole rescue of hemocyte function did not eliminate midline phenotypes compared with similarly staged control embryos, and a significant degree of rescue was achieved by Pvr expression in ectodermal derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…Presumably, the AS has to get out of the way before converging tissues meet at the midline, but inefficient hemocyte phagocytosis might result in corpses or debris obstructing the fusing tissues. Hemocytes also secrete extracellular matrix proteins required for embryonic morphogenesis (Bunt et al, 2010;Olofsson and Page, 2005). Together, impaired hemocyte survival and migration, two characteristic phenotypes of Pvr mutants (BrĂŒckner et al, 2004;Cho et al, 2002), could contribute to both decreased removal of cell corpses and compromised integrity of tissues fusing at the midline.…”
Section: Pvr Protein Expression In the As And Ectodermmentioning
confidence: 99%
“…For example, it has been shown in Xenopus that neural crest and placode cells undergo a 'chase and run' mode of migration, in which the neural crest cells chase placode cells through chemotaxis and placode cells run when they are contacted by neural crest cells (Theveneau et al, 2013). In Drosophila embryos, hemocytes and renal tubules undergo migrations that are temporally distinct, yet have been shown to guide each other's migration/ morphogenesis (Bunt et al, 2010). Interdependent cell migrations might be commonplace during development and, despite the limited temporal role of such interactions, these interactions are likely to contribute to the efficient and robust movement of cells that is required to support proper development.…”
Section: Interdependence Of Germ Cell and Cvm Cell Migrationsmentioning
confidence: 99%
“…Duchek et al, 2001;McDonald et al, 2006). However, in a few cases, it has also been found that distinct cell types can jointly influence each other's migration and/or morphogenesis (Bunt et al, 2010;Theveneau et al, 2013). Thus, directed cell migration may be regulated by a series of events that include fixed and/or moving cues.…”
Section: Introductionmentioning
confidence: 99%